The Gaia Basic angle: measurement and variations. Issue 67 (17th July 2015) - Mora, A.; Bastian, U.; Biermann, M.; Chassat, F.; Lindegren, L.; Serraller, I.; Serpell, E.; van Reeven, W.
Abstract : The ESA Gaia mission uses two telescopes to create the most ambitious survey of the Galaxy. The angle between them must be known with exquisite precision and accuracy. An interferometer: the Basic Angle Monitoring system measures its variations. High quality data have been retrieved and analysed for more than a year. A summary of the in-orbit performance and some early results are presented.